The growth and yield of maize (Zea mays L.) and soyabeans (Glycine max. (L) Merrill) grown as intercrops : a thesis presented in partial fulfilment of the requirement for the degree of Master of Agricultural Science in Plant Science at Massey University - Kamarudin, Yusoff (Massey University, 1986)
The effect of plant population maize (Zea mays L.) cultivar (Pioneer 3901) and AMT and Matara cultivars of soyabeans (Glucine max (L) Merill) grown together in an intercropping system was studied. In the experiment three rows of maize were sown at populations of 6, 8, 10 plants/m2 and three rows of soyabeans were planted between the rows of maize at either 50 or 75 plants/m2 replacing one of the three rows of maize. Plants were sampled for vegetative analysis during the growth of the crops and at final harvest. Total dry matter, grain yield and the components of yield and leaf area index were determined. Grain yield of maize increased from 794 to 1522 g/m 2 as the population of maize increased. However the yield of the maize was not affected by either the cultivar or the populations of the soyabeans grown among it. Grain yield and the component of yield of the intercropped soyabeans were not affected when population of maize in the mixture was increased. Matara produced higher yields than AMT when grown with maize and this was associated with production of more grain per plant and larger seeds. As the plant population of the soyabeans was increased the grain yield of Matara increased and up to 336.9 g/m2 was obtained, however the yield of AMT was not affected by a similar increase in plant population, possibily Matara had greater temporal difference and was more competative than AMT when grown in the mixture. Three methods were used to evaluate the yield of intercropped plots. These were the seed yield summed for both crops, Land Equivalent Ratio (LER) and a yield ratio based on maize. Although the results obtained depended on the method used all the three methods indicated intercropping could be more advantageous than growing maize and soya beans as pure stands. All the three methods indicated that the highest yield was obtained when the highest population of maize was combined with the highest population of soyabeans. Higher yields were obtained when Matara rather than AMT was grown in the intercropped plots.
Keywords: Corn; Soybean; Companion crops